A Small Protein but with Diverse Roles: A Review of EsxA in Mycobacterium–Host Interaction - Yanqing Bao; Lin Wang; Jianjun Sun (Cells, 2021)
As a major effector of the ESX-1 secretion system, EsxA is essential for the virulence of pathogenic mycobacteria, such as Mycobacterium tuberculosis (Mtb) and Mycobacterium marinum (Mm). EsxA possesses an acidic pH-dependent membrane permeabilizing activity and plays an essential role by mediating mycobacterial escape from the phagosome and translocation to the cytosol for intracellular replication. Moreover, EsxA regulates host immune responses as a potent T-cell antigen and a strong immunoregulator. EsxA interacts with multiple cellular proteins and stimulates several signal pathways, such as necrosis, apoptosis, autophagy, and antigen presentation. Interestingly, there is a co-dependency in the expression and secretion of EsxA and other mycobacterial factors, which greatly increases the complexity of dissecting the precise roles of EsxA and other factors in mycobacterium–host interaction. In this review, we summarize the current understandings of the roles and functions of EsxA in mycobacterial infection and discuss the challenges and future directions.